Representações da Colônia Cecília na ficção brasileira - Godk, Bruna Dancini (2013)
In the present study we intended to analyze the modes of fictional representation of Colônia Cecília, an anarchist experience of the nineteenth century, in two Brazilian novels: Colônia Cecília (1945), by Afonso Schmidt and Um amor anarquista (2005), by Miguel Sanches Neto. In order to this, we studied the production context of the two novels, as well as the internal consistency of these. To establish a parameter with the history, we used studies of Souza (1970) and Felicci (1998). In literature, studies by Bosi (1975) and Candido (2002) were indispensable. However, to study the affiliation of the research corpus, we made use respectively of Ridenti (2002) and Hutcheon (1991).